Local aspects of sleep and wakefulness. (June 2017) - Siclari, Francesca; Tononi, Giulio
Highlights: Slow waves of NREM sleep can occur locally and asynchronously across brain regions. Their regional distribution and amplitude is in part mediated by experience-dependent changes in synaptic strength. Local low-frequency oscillations (<10 Hz) can occur also in REM sleep and during wakefulness. Local low-frequency oscillations during wake lead to region-specific cognitive errors. Local changes in SWA in posterior brain regions account for changes in consciousness during sleep. Abstract : Slow waves, the hallmark of NREM (Non Rapid Eye Movement) sleep, are not uniformly distributed across the cortical surface, but can occur locally and asynchronously across brain regions. Their regional distribution and amplitude is affected by brain maturation and by time spent awake, mediated in part by experience-dependent changes in synaptic strength. Recent studies have shown that local low-frequency oscillations (<10 Hz) can also occur in REM sleep and during wakefulness, leading to region-specific cognitive errors. Local decreases and increases of slow wave activity in posterior brain regions have been linked to the occurrence of dreaming and to unconscious sleep, respectively. Finally, the coexistence of local sleep-like and wake-like patterns in different brain areas is characteristic of several sleep disorders and may offer insights into these conditions.